Effect of Heat Stress on Body Weight Gain, Heterophile-Lymphocite Ratio and Body Temperature in Broiler - Sugito S; Mira Delima (Universitas Syiah Kuala, 2009)
Increasing in ambient temperature inside the cage could lead to heat stress in broilers. This research was conducted to find out effects of heat stress on body weight gain, heterophile-lymphocite ratio and body temperature in chicken broiler. Twenty broilers aged 20 days (strain Cobb) were randomly divided into 2 groups. The first group was treated with no heat stress, the second one was caged in 33±1 0C temperature for 4 hours per day for 14 days. The results indicated that heat stress reduced body weight gain, increased body temperature, and changed behavior, but no effect on feed conversion ratio (FCR) and heterophile-lymphocyte ratio. It suggested that the heat stress caused detrimental effects on broiler chicken.